Epigenetics at the crossroads of secondary growth regulation - Inácio, Vera; Santos, Raquel; Prazeres, Rafael; Graça, José; Miguel, Célia M.; Morais-Cecílio, Leonor (Frontiers in Plant Science, 2022)
The development of plant tissues and organs during post-embryonic plant growth occurs through the activity of both primary and secondary meristems. While primary meristems (root and shoot apical meristems) promote axial plant growth, secondary meristems (vascular and cork cambium or phellogen) promote radial thickening and plant axes strengthening. The vascular cambium forms the secondary xylem and phloem whereas the cork cambium gives rise to the periderm that envelops stems and roots. Periderm takes on an increasingly important role in plant survival under climate change scenarios, but it is also a forest product with unique features, constituting the basis of a sustainable and profitable cork industry. There is established evidence that epigenetic mechanisms involving histone post-translational modifications, DNA methylation, and small RNAs play important roles in the activity of primary meristem cells, their maintenance, and differentiation of progeny cells. Here, we review the current knowledge on the epigenetic regulation of secondary meristems, particularly focusing on the phellogen activity. We also discuss the possible involvement of DNA methylation in the regulation of periderm contrasting phenotypes, given the potential impact of translating this knowledge into innovative breeding programs.